Countdown to CQUniversity: An Analysis of a Student-Driven Program Designed to Help Students Transition to University, Before They Start University - Burt, Malcolm; Forman, Marie; James, Trixie; Pienaar, Josua (Journal of Education and Learning Environments, 2026)
The transition into university study can be challenging, particularly for students from non-traditional backgrounds who may lack cultural capital or familiarity with academic expectations. As one of Australia’s largest regional universities, with a presence in every mainland state, and with the distinction of being Queensland’s only dual-sector university, CQUniversity’s (Central Queensland University) commitment to regional engagement, inclusivity and flexible study options means that many of our diverse student body in excess of 30,000 encounter these challenges. In response, CQUniversity co-designed a pre-term early intervention program, Countdown to CQUniversity, using a participatory action research (PAR) approach that actively incorporated the student voice into all stages of development. The program comprises five short online modules addressing orientation, time management, academic integrity, critical thinking, and the learning management system. This study reports on the program’s development, pilot implementation, and evaluation. Pre- and post-survey data demonstrated substantial increases in students’ familiarity with key academic concepts, while qualitative findings highlighted enhanced confidence, perceived preparedness, and appreciation of the program’s accessibility and relevance. The results indicate that student co-created early intervention programs can improve readiness, support transition, and contribute to more consistent institutional messaging. Implications for the design of orientation resources, integration of student voice, and future research directions are discussed.